Individual and family motivational intervention for treatment of alcohol abuse - López-Beltrán, Iván; Pedroza-Cabrera, Francisco Javier; Martínez-Martínez, Kalina Isela; de la Roca-Chiapas, José María; Carranza-Jasso, Rodrigo (Gaceta Médica de Caracas, 2021)
Alcohol abuse is one of four non-communicable diseases that kill 70 % of the world’s population, damaging the individual and his family’s functionality. This project’s objective was to evaluate the effectiveness of family versus individual alcohol abuse intervention using a transtheoretical model and motivational interview. El abuso de alcohol es una de las cuatro enfermedades no transmisibles que matan al 70 % de la población mundial y dañan al individuo y la funcionalidad des u familia.